2021
DOI: 10.3390/diagnostics11020288
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Subgenomic N (sgN) Transcripts in Oro-Nasopharyngeal Swabs Correlate with the Highest Viral Load, as Evaluated by Five Different Molecular Methods

Abstract: The COVID-19 pandemic has forced diagnostic laboratories to focus on the early diagnostics of SARS-CoV-2. The positivity of a molecular test cannot respond to the question regarding the viral capability to replicate, spread, and give different clinical effects. Despite the fact that some targets are covered by commercially-available assays, the identification of new biomarkers is desired in order to improve the quality of the information given by these assays. Therefore, since the subgenomic transcripts (sgN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 27 publications
2
34
1
Order By: Relevance
“…Whether persistent levels of sgRNA are actual proof of infectivity is still unclear; however, negative sgRNA can indicate that subjects are not infectious [ 22 ]. To date, previous studies reported evidence regarding the detection of viral sgRNAs using sequencing, RT-PCR and ddPCR, and all these findings were based on non-vaccinated cases [ 8 , 23 , 24 ]. The detection of viral sgRNA coupled with an increased viral load has been shown to be indicative of an aggravation of the disease [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether persistent levels of sgRNA are actual proof of infectivity is still unclear; however, negative sgRNA can indicate that subjects are not infectious [ 22 ]. To date, previous studies reported evidence regarding the detection of viral sgRNAs using sequencing, RT-PCR and ddPCR, and all these findings were based on non-vaccinated cases [ 8 , 23 , 24 ]. The detection of viral sgRNA coupled with an increased viral load has been shown to be indicative of an aggravation of the disease [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of COVID-19 vaccination campaigns, it is highly important to understand the base of evidence regarding vaccine effectiveness in preventing symptomatic and asymptomatic infections and transmission from infected individuals to susceptible contacts. Investigating both viral genomic and subgenomic RNAs in subjects infected with SARS-CoV-2 might be relevant for epidemiology purposes and infection control, with potential for clinical significance mainly related to the duration of the disease [ 24 ]. The detection of sgRNAs can provide useful data when combined with routine assays based on the detection of viral gRNA, particularly to assess the phase (early vs. late) of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Note also that transcription of the main SARS-CoV-2 sgRNAs was also impaired (e.g., sgN ). Thus, we suggest that polyPs reduce active viral replication ( 34 ). This antiviral action was also seen with mutations in the S gene, which enhanced viral infectivity and fitness; this further supports the potential for the use of polyPs to inhibit different emerging variants of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 88%
“…All tests were performed within Lab n. 777777 of CEINGE Biotecnologie Avanzate S.C.a R.L., belonging to the CORONET Campania Regional network. Briefly, Real-time reverse transcriptase-polymerase chain reaction (RT-PCR) was performed by Allplex SARS-CoV-2 assay (Seegene, Seoul, Korea) as already reported by our group ( 9 ), according to manufacturer’s instructions, on the NSF deriving RNA of our patient. The study was approved by the Ethical Committee of the University Federico II of Naples (authorization n.180/20/ES1 on 25.05.2020) and was performed in compliance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%